Interfaith etiquette in an age of Islamophobia. Issue 3 (17th July 2019) - Green, Todd
Abstract: Islamophobia represents one of the greatest moral dilemmas of our time. Anti‐Muslim hostility and hatred, driven by racism, has manifested itself in exclusionary, discriminatory, and violent actions toward Muslims and those perceived as Muslims. By most metrics, Islamophobia in the United States is only getting worse. This article draws on Krister Stendahl's rules of interfaith engagement as a means of offering Christians a blueprint for how to reach out and engage with their Muslim neighbors in an age of Islamophobia.